Investigating the monotonic behaviour of hybrid tripod suction bucket foundations for offshore wind towers in sand. (August 2019) - Faizi, Koohyar; Faramarzi, Asaad; Dirar, Samir; Chapman, David
Abstract: Existing tripod suction bucket foundations, utilised for offshore wind turbines, are required to resist significant lateral loads and overturning moments generated by wind and currents. This paper presents an innovative type of tripod bucket foundation, 'hybrid tripod bucket foundation', for foundations of offshore wind turbines, which has the ability to provide a larger overturning capacity compared with conventional tripod buckets. The proposed foundation consists of a conventional tripod bucket combined with three large circular mats attached to each bucket. A series of experiments were conducted on small-scale models of the proposed foundation subjected to overturning moment under 1g conditions in loose sand. Different circular mat diameter sizes with various bucket spacings were considered and the results were compared with conventional tripod bucket foundation. Finite element models of the proposed foundation were developed and validated using experimental results and were used to conduct a parametric study to understand the behaviour of the hybrid tripod bucket foundation. The results showed that there is a significant increase in overturning capacity provided by the novel foundation. The results of this work can significantly improve lowering the costs associated with installation of foundations to support offshore wind turbines.